SOSIALISASI KARIR DAN PROFESI LULUSAN AKUNTANSI DALAM DUNIA BISNIS PADA SMA NEGERI 1 BANTARSARI - Giovanny Bangun Kristianto; Farida Istiningrum; Lusi Yuliarti (Archipelago, 2023)
Accounting graduates from high school and vocational students certainly have the goal of getting a better career for their future. College level is also one of the stepping stones before entering the world of work. Accounting graduates from a University or College of Accounting will make them more ready to work and have added value for the individual. This Community Service is packaged in a socialization which is given to students of Bantarsari 1 State High School, Cilacap Regency, who are already in class XII, both science and social studies classes. The number of students who took part in the socialization reached approximately 150 students consisting of 3 science classes and 2 social studies classes, which were held in a multipurpose room at SMAN 1 Bantarsari Cilacap. Socialization is provided by providing information about the professions in the accounting profession such as corporate accountants, public accountants, auditors, tax accountants and government accountants. Other information provided such as the type of work performed and the estimated amount of salary that will be received by each in that profession. The information provided is also related to the accounting cycle starting from business transactions to the preparation of a financial report for the company.Keyword: Accountant, Proffesional, graduated